Kebangkitan Nasional Landasan Penting Dalam Pendidikan Islam di Indonesia - Ismail Triyanto; Sukari (Al-Abshor : Jurnal Pendidikan Agama Islam, 2024)
Abstract This research is a library research that aims to strengthen the understanding of the strategic role of education in building and maintaining the spirit of nationalism that has been instilled since the National Awakening era. The methodology in this research is to collect data from articles, books, and journals, as well as information from other internet sources originating from credible sources. After the data is collected, it is reduced by reading the abstract, if it is not relevant to the topic of discussion, it is eliminated. And if after reading the abstract, it is relevant to the topic of discussion, it is read in its entirety and compiled in a reference manager to facilitate the management of reference sources. The results of this study indicate that the National Awakening is an important historical milestone for Indonesia that marks the spirit of struggle and awareness of national identity. This study explores how the spirit of National Awakening influences and shapes the education system in Indonesia. Through historical studies and contemporary analysis, this study highlights the role of education in strengthening the spirit of nationalism as well as the challenges and opportunities faced in the context of globalization.  Abstrak Penelitian ini merupakan penelitian kepustakaan (library research) yang bertujuan memperkuat pemahaman tentang peran strategis pendidikan dalam membangun dan mempertahankan semangat Kebangsaan yang telah ditanamkan sejak masa Kebangkitan Nasional. Metodologi dalam penelitian ini adalah dengan mengumpulkan data-data dari artikel, buku-buku, dan jurnal, serta informasi dari internet lainnya yang berasal dari sumber yang kredibel. Setelah data terkumpul direduksi dengan cara dibaca pada abstraknya, bila tidak relevan dengan topik pembahasan maka dieliminasi. Dan apabila setelah dibaca pada abstraknya ada relevansinya dengan topik pembahasan maka dibaca secara keseluruhan dan dihimpun dalam reference manager untuk mempermudah dalam mengelola sumber-sumber referensi. Hasil dari penelitian ini menunjukkan bahwa kebangkitan nasional merupakan tonggak sejarah penting bagi Indonesia yang menandai semangat perjuangan dan kesadaran akan identitas kebangsaan. Penenlitian ini mengeksplorasi bagaimana semangat kebangkitan nasional mempengaruhi dan membentuk sistem pendidikan di Indonesia. Melalui kajian historis dan analisis kontemporer, penelitian ini menyoroti peran pendidikan dalam memperkuat semangat kebangsaan serta tantangan dan peluang yang dihadapi dalam konteks globalisasi.